The Theatre of Bauhaus - Decheva, Violeta (Sledva : NBU Journal of Humanities and Arts, 2020)
How Bauhaus movement informs not only modern architecture but also modern theatre, dance, art, music, the structure of the stage, the idea of the space, etc.? The ‘theatre of Bauhaus’ is not a clear system of ideas shared by all the participants in the movement. On the contrary, there are many internal conflicts. But we could speak of concepts that were developed and became influential through Bauhaus, especially after the ‘branding’ of the movement in the US in the second half of 20th century.